The Acehnese Literature and Social Behavior - Fitriya Munidar (Winaya Inspirasi Nusantara Foundation, 2024)
This research essay analyzes the relationship between Acehnese literature and social behavior. Writing in Acehnese has served as a vehicle for contemplating Aceh's political and human conditions, particularly in the aftermath of the tsunami and post-conflict periods. With data from sociolinguistic analysis, netnography interviews, and literature evaluations, the study used a descriptive qualitative research approach. The results demonstrate that reading Acehnese literature can be seen as both a cultural battle within the reading community and a vehicle for political purification and introspection. Along with these language variations, the study looks at slang, idiolect, dialect, and acrolectal in both North and West Acehnese. According to the report, there are active Acehnese groups in Malaysia that participate in social events, such as celebrating Islamic holidays. The survey also indicated that the use of local language in public spaces like as coffee shops is still less desirable amongst youth in Aceh. The study comes to the conclusion that social behavior and cultural identity are strongly correlated with Acehnese language and literature.